2019
DOI: 10.5455/ajvs.29544
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Autophagy as Possible Mechanism of the Antitumor Effects of Arsenic Trioxide and/or Cisplatin on Ehrlich Ascites Carcinoma Model

Abstract: 1. INTRODUCTION Arsenic trioxide (ATO), have a noticeable therapeutic effect on solid tumor cell, lines, such as cervical cancer cells, human sarcoma cells, hepatoblastoma cells and HCC cells. ATO treatment activated both p38 MAPK and JNK pathway in Hela cells. Activation of MAPKs, such as p38 MAPK and JNK, were important for cancer prevention by drug therapy against cancer (Xia et al., 2018). Autophagy is a lysosome-dependent cellular degradation process that has functions in nutrient recycling and energy gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…This was represented by large nodules in the peritoneal cavity and metastatic changes in the liver parenchyma, evidenced by atypical epithelial cells with large hyperchromatic nuclei with many mitotic activities (Figures S4 and S5, GII). Such findings were related to the high viability, mobilization, and metastatic probability of the used tumor cell line, and they were in accordance with the observation of Chakraborty et al, (2007) and Mansour et al, (2019),who reported similar histopathologic changes in mice that received EAC only [90,91].…”
Section: Histopathological Findingssupporting
confidence: 91%
“…This was represented by large nodules in the peritoneal cavity and metastatic changes in the liver parenchyma, evidenced by atypical epithelial cells with large hyperchromatic nuclei with many mitotic activities (Figures S4 and S5, GII). Such findings were related to the high viability, mobilization, and metastatic probability of the used tumor cell line, and they were in accordance with the observation of Chakraborty et al, (2007) and Mansour et al, (2019),who reported similar histopathologic changes in mice that received EAC only [90,91].…”
Section: Histopathological Findingssupporting
confidence: 91%